Pseudoaneurysm of Facial Artery after Orthognathic Surgery - Neto, Tiburtino José De Lima [UNESP]; Maranhão, Carlos Alexandre De Albuquerque; Neto, Patrício José De Oliveira (Wolters Kluwer, 2019)
Sagittal osteotomy of the mandibular branch is to be included common approach for alteration of facial tooth shapes and it is treated technically safe. This conduct can breed various complications, among other things vascular complications. A clinical case has described the development of pseudoaneurysm in the facial artery in a 33-year patient undergoing bilateral osteotomy Le Fort I sagittal osteotomy of the mandibular branch. Subsequently, there was a vascular complication treated by the vascular surgeon that generated a rejection process to the material used for treatment, generating aesthetic damage to the patient and the need for plastic surgery intervention. The leading mode of conduct of vascular injuries are analyzed, and embolization is established to be technically secure conduct.
Keywords: Embolization therapeutic; orthognathic surgery; vascular surgical procedures